Penggunaan Animasi Powerpoint dan Prezi pada Mata Kuliah Geometri Euclide di Perguruan Tinggi - Widiawati Widiawati; Indah Widyaningrum (Jurnal Pendidikan Matematika:Judika Education, 2020)
The purpose of this study was to find out the effect of using PowerPoint animation and Prezi usage on student learning outcomes and compare the differences between student learning outcomes using PowerPoint animation and Prezi. The method used is an experimental method with the Pattern Pretest-Posttest Control Group Design. The population in this study was all undergraduate students of Mathematics Education Study Program semester II at STKIP Muhammadiyah Pagaralam with a sample of two classes. Data collection techniques used are documentation and tests. Test data were analyzed through normality test calculation, homogeneity test, average one test and two average test with calculation using SPSS for windows. The results showed that there is an influence of using PowerPoint animation with ρ value 0.000 and Prezi ρ value 0.032 with student learning results and there is a difference between student learning outcomes using PowerPoint animation with Prezi with ρ value 0.006. In conclusion, there is a significant influence of the use of PowerPoint and Prezi animations on student learning outcomes and there are noticeable differences between the learning outcomes of students using PowerPoint animation and Prezi. The average student learning outcomes using PowerPoint animation are better than Prezi's. Keywords: PowerPoint animation, Learning Outcomes, Prezi